Bank Diversification Effects on Bank Performance and Risk Profile of Bank in Indonesia - Anthony Lukmawijaya; Sung Suk Kim (DeReMa (Development Research of Management): Jurnal Manajemen, 2015)
We investigate the relationship of Indonesian bank diversification towards its long term performance and risk profile with Indonesian bank data from 2009 to 2013. Non-interest income to total operating income of the bank measures its bank diversification level. Bank value is measured by the adjusted Tobin's Q and risk profile which is broken down into total risk, idiosyncratic risk, and systematic risk. The result shows that bank non-interest income diversification has a positive influence on its franchise value. There is, however, no strong evidence that diversification can lower a bank's risk profile.